The Description of Worker’s Compliance in Wearing Personal Protective Equipment in Madubaru Inc - Ratna Lestari, Ratna Lestari; Agus Warseno (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2021)
Potential hazards in the workplace can threaten the safety of employees at PT Madubaru. The hazards include burns, heat stress, falling from the grinding floor, and crushing hands in the mill. These hazards can be prevented by complying with the rules set by the company, one of which is using personal protective equipment (PPE). Worker’s compliance can be influenced by internal factors such as sociodemography. This study aims to determine the description of worker compliance in using PPE at PT Madubaru seen from the characteristics of workers including age, employment status, education, length of work, and participation in counseling. This study used quantitative research methods with a descriptive design in the form of a survey. Samples were taken by purposive sampling technique, included 86 workers in the evaporation and milling unit. Data were collected using a demographic data questionnaire and a checklist sheet for compliance with the use of PPE. Data analysis was performed by displaying the frequency and percentage. The results show 76.7% of workers were not compliant in using PPE. Non-compliance by age was dominated by young adults (18-40 years) of 45.3%, based on education was dominated by high school education (66.3%), length of work ≥ 5 years was 64%, temporary workers about 59.3%, and based on participation in the PPE counseling was dominated by workers who never attended by 64%.